2020
DOI: 10.1016/j.cmi.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Clostridioides difficile hypervirulent ribotype 027 spore germination, vegetative cell growth and toxin production in vitro

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…We showed that communities that reduce the external pH below 6.2 inhibit C. difficile in a pH‐dependent manner, consistent with studies showing that C. difficile has lower viability and rates of sporulation in acidic environments (Wetzel & McBride, 2020; Yuille et␣al , 2020). We note that our in␣vitro system differs from the human gut, lacking the pH‐buffering secretion of bicarbonate by host intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We showed that communities that reduce the external pH below 6.2 inhibit C. difficile in a pH‐dependent manner, consistent with studies showing that C. difficile has lower viability and rates of sporulation in acidic environments (Wetzel & McBride, 2020; Yuille et␣al , 2020). We note that our in␣vitro system differs from the human gut, lacking the pH‐buffering secretion of bicarbonate by host intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
“…For example, communities with the same richness invaded with equal abundances of C. difficile showed a wide range of C. difficile abundances at 48 h (Fig 2A). Since environmental pH has been shown to influence C. difficile ’s growth in previous studies (Wetzel & McBride, 2020; Yuille et␣al , 2020), we turned next to investigate how biotic modification of the environment alters the growth of C. difficile . To this end, we grew the set of 15 3–4 member communities for 6 h before invading with low or high initial densities of C. difficile to give the communities time to modify the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that communities can inhibit growth of C. difficile by acidifying the environment. We showed that communities that reduce the external pH below 6.2 inhibit C. difficile in a pH-dependent manner, consistent with studies showing that C. difficile has lower viability and rates of sporulation in acidic environments 33,34 . While our in vitro system lacks the pH-buffering secretion of bicarbonate by host intestinal epithelial cells, the amount of bicarbonate buffer in our media (4.8 mM) is within the estimated range in the gastrointestinal tract (2-20mM) 45 , suggesting the observed pH changes in our media could be physiologically relevant.…”
Section: Difficilesupporting
confidence: 89%
“…2a). Since environmental pH has been shown to influence C. difficile's growth in previous studies 33,34 , we turned next to investigate how biotic modification of the environment alters the growth of C. difficile. To this end, we grew the set of 15, 3-4 member communities for six hours and then invaded with low or high initial densities of C. difficile.…”
Section: Environmental Ph Is a Major Factor Influencing C Difficile Growth In Synthetic Communitiesmentioning
confidence: 99%
“…They affect host physiology, including an energy source for colon cells, regulating the intestinal barrier, and affecting inflammatory responses ( Correa-Oliveira et al, 2016 ). SCFAs also inhibit C. difficile toxin production ( Yuille et al, 2020 ), reducing CDI ( McDonald et al, 2018a ; Fachi et al, 2020 ) and inhibiting spore growth ( Battaglioli et al, 2018 ; Hryckowian et al, 2018 ; Neumann-Schaal et al, 2019 ). Like previous studies ( McDonald et al, 2018a ), the CDI group showed decreased butyric acid, propionic acid, acetic acid, and A. muciniphila restored SCFA metabolism, possibly by restoring the intestinal flora balance.…”
Section: Discussionmentioning
confidence: 99%